Driving Village-Owner Enterprises (BUMDes) Innovation as a Driving Force for Independent Village Development Through Inclusive Leadership - Hakim, Muhammad Lukman; Agung, Magda Faradiba Mauludia; Hanif, Nita Aribah; Firman, Firman (Journal of Social Contemplativa, 2024)
This study examines the role of inclusive leadership in driving innovation within Village-Owned Enterprises (BUMDes) as a catalyst for self-reliant village development in Indonesia. The research employed a qualitative approach with case studies of BUMDes in Kulon Progo, Gunung Kidul, and Yogyakarta City. The study aims to analyze the dynamics of the innovation process in BUMDes and the innovation leadership models in place. Findings indicate that inclusive leadership accelerates innovation by empowering local communities, fostering collaboration, and creating a safe environment for experimentation. Case studies in Kulon Progo and Gunung Kidul demonstrate that successful product, process, marketing, and organizational innovations can enhance local economic growth, community welfare, and environmental sustainability. Strategies for promoting inclusive leadership include capacity building, community engagement, mentorship programs, and recognition. This research positively contributes to the study of innovation in BUMDes and offers practical insights for developing inclusive leadership models across various bureaucratic levels in Indonesia.